(untitled) - Burns, Anne (Cambridge, U.K., 1999)
This book proposes that action research should be a collaborative process emerging from the practical concerns of groups of teachers working in a common or similar context. Teachers' first-person accounts provide the basis for exploring the challenges and constraints of action research. The book will be of interest to teachers seeking new directions for their own professional development as well as others interested in integrating collaborative action research into current practice and curriculum renewal.
Keywords: Action research in education,English language,English language; Discourse analysis,Study and teaching,Foreign speakers